A hybrid analysis model supported by machine learning algorithm and multiple linear regression to find reasons for unemployment of programmers in Iraq - Mohamed A. Abdulhamed; Hadeel I. Mustafa; Zainab I. Othman (Universitas Ahmad Dahlan, 2021)
The problem of unemployment is one of the most important problems faced by most countries of the world, and it is one of the intractable problems in developing countries, and in Iraq unemployment occupies great importance due to its high rates. This problem in itself is a serious condition, because it results from mismanagement and the structure of the economy, and despite its great importance, it has not been carefully monitored. There are studies and strategies that deal with the analysis and study of those causes that lead to this problem, such as traditional statistical methods, various mathematical and statistical methods, in this research proposed a method uses machine learning methods to find the factors that affect the causes of this problem, as well as the multiple linear regression method.